2000
DOI: 10.1074/jbc.m003299200
|View full text |Cite
|
Sign up to set email alerts
|

Specific Sequences of the Sm and Sm-like (Lsm) Proteins Mediate Their Interaction with the Spinal Muscular Atrophy Disease Gene Product (SMN)

Abstract: The spinal muscular atrophy disease gene product (SMN) is crucial for small nuclear ribonuclear protein (snRNP) biogenesis in the cytoplasm and plays a role in pre-mRNA splicing in the nucleus. SMN oligomers interact avidly with the snRNP core proteins SmB, -D1, and -D3. We have delineated the specific sequences in the Sm proteins that mediate their interaction with SMN. We show that unique carboxyl-terminal arginine-and glycine-rich domains comprising the last 29 amino acids of SmD1 and the last 32 amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(116 citation statements)
references
References 59 publications
4
112
0
Order By: Relevance
“…4 and 5), and other studies indicate that SMN also interacts with hnRNP U (34), several Sm and Sm-like (Lsm) proteins (23,36,41,44,62), and RNA helicase A (30) via glycine/arginine-rich domains. On the other hand, the interaction between the Caenorhabditis elegans SMN and fibrillarin homologs in a yeast two-hybrid system was found to be independent of the GAR domain of fibrillarin (63).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…4 and 5), and other studies indicate that SMN also interacts with hnRNP U (34), several Sm and Sm-like (Lsm) proteins (23,36,41,44,62), and RNA helicase A (30) via glycine/arginine-rich domains. On the other hand, the interaction between the Caenorhabditis elegans SMN and fibrillarin homologs in a yeast two-hybrid system was found to be independent of the GAR domain of fibrillarin (63).…”
Section: Discussionmentioning
confidence: 92%
“…This finding is of potential importance to our understanding of snoRNP biogenesis as well as the etiology of spinal muscular atrophy. SMN interacts with fundamental components of multiple nuclear RNA-protein complexes as follows: spliceosomal snRNPs (23,35,36,41,44), Box C/D snoRNPs (this work), and also Box H/ACA snoRNPs. 3 The interaction of SMN with each of these RNPs occurs by a similar mechanism involving the Tudor domain of SMN (Refs.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previously, we showed that the C-terminal 214 amino acid (aa) residues of coilin are sufficient for interaction with SmB′, making coilin a candidate (Hebert et al 2001). Since we had not previously defined the region of SmB′ that interacts with coilin, we were specifically interested in assessing if coilin binds SmB′ at a location distinct from SMN, which predominantly binds to the RG-rich tails of Sm proteins (Brahms et al 2001;Friesen and Dreyfuss 2000;Selenko et al 2001). We therefore generated two His-T7-tagged SmB′ truncations; one truncation deletes all of the RG dipeptides found in the C-terminal tail, whereas the other construct leaves approximately half of them.…”
Section: Coilin Binds To the Sm-fold Regions Of Sm And Sm-like Proteinsmentioning
confidence: 99%
“…Tudor domains have highly conserved amino acids and predicted structure, which suggests that the structure of the Tudor domain in SMN is likely to be very similar to those found in other Tudor domain containing proteins. SMN binds to two SM proteins, SmD1 and SmD3, at their carboxy-terminal ends, which are arginine-and glycine-rich domains [39]. Methylation of the carboxy-terminal ends of SmD1 and SmD3 enhances the binding ability of SMN by several folds.…”
Section: A Brief Analysis Of Tudor Domainsmentioning
confidence: 99%